The Construction of Onomatopoeia Through Visual Features in Avatar: The Last Airbender – The Promise Comic - Hamdi Pratama Al Wiradani; Rahajeng Chintami Evananda Desnita Rachmalia; Euis Meinawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Onomatopoeia in comics is often viewed primarily as phonetic imitation, with limited attention to its visual semiotic construction. This study examines how typographic, positional, and chromatic features systematically construct onomatopoeic expressions in twenty selected panels from Avatar: The Last Airbender – The Promise (2012). Employing qualitative content analysis, the research integrates Peirce’s triadic semiotic model (representamen–object–interpretant) with Kress and van Leeuwen’s visual grammar. Findings reveal that typography iconically mimics sound qualities (e.g., jagged forms for intensity), placement creates indexical vectors simulating motion and causality, and colour modulates emotional and symbolic interpretation (e.g., warm hues for fire related violence, cooler tones for air/earth elements). These features converge to enhance sensory immersion and reinforce the narrative’s postcolonial themes of power, trauma, and reconciliation. Unlike prior studies emphasising auditory or typological aspects, this research proposes a comprehensive multimodal framework, advancing comic semiotics and visual meaning-making in graphic storytelling.